Consulta de enfermagem motivacional com alcoolistas: o cuidado no processo de mudança - Subrinho, Lucas Queiroz (2024)
Objective: To evaluate the effectiveness of the Motivational Nursing Consultation (CEM) in changing the behavior of alcoholics in a specialized outpatient care program at a university hospital. Methods: a quantitative, analytical, clinical, pre-experimental, longitudinal research with three moments of variable measurement. The participants were users of the Alcohol Outpatient Program of the Cassiano Antônio Moraes University Hospital of the Federal University of Espírito Santo (PAA-HUCAM-UFES), referred to the CEM, who self-reported episodes of alcohol consumption within the last 30 days, without a history of treatment by the service nurse. A total of 21 users who participated in five CEM in 90 days were included. Behavior changes were evaluated at three moments: before the intervention, in the day of the third CEM, and after the fifth CEM. Through a questionnaire composed of a biosocioeconomic and demographic survey, Depression, Anxiety and Stress Scale - Short Form (DASS-21), Short Alcohol Dependence Data (SADD), Questionnaire of Perceived Changes, brazilian version (QPC) and two adaptations of standardized instruments in the international scenario Quick Drinking Assessment Interview (FORM-90-AQ) and Readiness to Change Ruler. Data analysis was performed through relative frequency, absolute, mean and standard deviation, paired t-test and routines executed in the statistical package Stata (Stat Corp®) version 12 for effect size calculation. This study is a subproject of the umbrella project entitled “Atenção a Usuários de Álcool, Tabaco e outras Drogas num Hospital Universitário: tecendo a rede do cuidar”, approved under appearance no. 5,558,775 and CAAE: 06800219.8.0000.5071 in the Research Ethics Committee of Hucam. Results: The pattern of consumption days was reduced in all evaluated periods, with a larger effect size between T0 and T2. The same behavior was observed in the reduction of heavy consumption. There was a reduction in score and severity in signs and symptoms of depression and stress between T0 and T2. SADD also showed a score reduction, while QPC had an increase. No effects were observed on the signs and symptoms of anxiety and readiness for change. Conclusion: The CEM was effective in changing the behavior of alcoholics in terms of consumption pattern, signs and symptoms of depression and stress, SADD and perceived change in relation to treatment. It is a low-cost approach that can be applied in the care of alcoholics.